Optimization noise figure of fiber Raman amplifier based on bat algorithm in optical communication network - Ali Abed Al-Asadi, Hamid; Ali Al-Asadi, Majida; Ali Noori, Nada (International Journal of Engineering and Technology, 2018)
Designing Raman amplifier with high On-Off again and low noise figure is required in in optical communication networks, due to wide and tunable amplification and low nonlinearity. This paper proposes a new configuration design to the single mode fiber Raman amplifier using a multi-objective bat algorithm. The main aim of the proposed method is to preserve the values of noise figure and ripple of the amplifier as low as possible while keeping the values of laser wavelength and the amplifier powers are high. The simulation results show that increasing the number of iterations is required, which would result in a flat gain spectrum with a considerable enhancement in the noise figure and minimal gain ripple that reaches to less than 0.18 DB.Â Â